100% KATOLIK 100% INDONESIA: Suatu Tinjauan Historis Perkembangan Nasionalisme Umat Katolik di Indonesia - Samudra Eka Cipta (Jurnal Sosiologi Agama, 2020)
Since the arrival of the Portuguese to Indonesia, many missionaries have spread Catholicism in Indonesia. The Maluku region became the beginning of the Catholicsm process in Indonesia, when a Portuguese missionary Francis Xavier came to the largest spice producing region in the world at that time. Previously, the arrival of the Portuguese in Indonesia in addition to their trade also brought religious interests in it. In 1546-1547 when he arrived in Maluku, he had succeeded in baptizing thousands of people also building schools for the indigenous population. When the VOC, which incidentally was a follower of Protestantism, tried to protest the population in the archipelago. They also sought to monopolize religion by mastering Catholic churches from Portuguese Spanish heritage, bearing in mind that in Europe there had been a strong push by Protestants against Catholics so that the impact of the Protestant-Catholic feud reached the Archipelago. Apparently, the era of Colonial Government began to be implemented after the fall of the VOC has had a tremendous impact on the development of Catholicism in Indonesia with the emergence of a spirit ‘'Catholic Awakening Indonesia'’ in line with the period of the emergence of Indonesian movement organizations in achieving Free Indonesia. This is inseparable from the role and emergence of several Indonesian Catholic figures in the political field including Ignasius Kasimo, and M.G.R Soegijapranata, even military fields such as Adi Sucipto and Slamet Riyadi who are among the leaders among Indonesian Catholics who defend for the sake of the nation and state of Indonesia.